Examination of Signal Intensity According to the Alteration of Contrast Media Concentration during Computed Tomography - Jeong, Sung-Hun; Lim, Cheong-Hwan (International Journal of Psychosocial Rehabilitation, 2020)
Background / Objectives: Generally speaking, it is shown that many medical institutions use contrast agents for both children and adults without distinguishing the concentration of the contrast agent, and many healthcare providers use the same contrast agent regardless of the examination site as identified on the patient. This is a factor that can increase the side effects by proceeding the test without considering the sensitivity, the concentration of the contrast agent, the injection speed, etc., depending on the patient’s constitution that causes the side effects of the contrast agent. For this reason, the purpose of this study is to obtain the image according to the concentration of CT contrast agent and test condition, to identify the change in signal intensity, and to determine the appropriate test condition according to the contrast agent concentration and to provide the study results thereof as the basic material in the study on the image concentration according to the change of the test condition. Methods / Statistical analysis: The equipment used in this study was MDCT and contrast agents were used at concentrations of 250, 300, 320, 350, 370, and 400mgI/ml. In this case, the contrast agent was measured after placing the Conical Tube on the table of MDCT without dilution. Here, the measurement conditions were measured at 37, 75, 100, 150, 320mAs for tube current mAs and 80, 100, 120, 135kVp. Findings: The findings revealed that as the tube voltage increased at tube currents of 75mAs, 100mAs, 150mAs, and 320mAs, the signal strength of the image was noted to be lowered in this case. In addition, the signal strength of the image was lowered as the tube voltage increased according to the contrast agent concentration. Improvements / Applications: It is considered that further studies will be needed for the test protocols that can lead to the improvement of the image quality safely and steadily, as the study of the appropriate contrast agent concentration and the test conditions for each test is continued to help improve patient outcomes. Keywords- Iodide contrast agent, Signal Intensity, Contrast agent side effects, Contrast Concentration, Computed Tomography